CURRENT-VOLTAGE CHARACTERISTICS OF SOLAR CELLS p-n JUNCTION ZnO AND TiO2 PARAREL ON Cu2O LAYER - Fadlly, Teuku Andi; Putra, Rachmad Almi (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2019)
Current-Voltage Characteristics of solar cells p-n junction ZnO and TiO2 parallel in the Cu2O layer has been determined using solar irradiation. Metal oxide has been used as a semiconductor material, such as ZnO and TiO2 is an n-type semiconductor. The material has a gap energy of 3.37 eV and 3.2 eV. Thermal oxidation is applied to commercial Cu plates for 60 minutes to produce Cu2O layers as p-type semiconductors. The process varies in temperature, namely 300, 400, and 500 Â°C. The process of thermal oxidation on Cu plates at a temperature of 300 Â°C increases the impurity in the Cu2O layer. The impurity layer is CuO. Then the CuO layer formed decreases with increasing temperature thermal oxidation. CuO layer increases the efficiency of solar cells p-n junction TiO2-ZnO parallel in the layer Cu2O. The results of measurements with sunlight showed that the TiO2-ZnO/Cu2O (300) samples had the highest solar cell efficiency, which was 0.28 %.